Glycemic control amongst diabetic subjects on insulin therapy: Still off target! - Surekha Bhujanga Shetty; Lalitha Ramachandrappa (International Journal of Medical Research and Review, 2019)
Introduction: Prevalence of diabetes is increasing worldwide. Good glycemic control is essential for prevention of complications of diabetes. Despite of availability of multiple medications, it is difficult to achieve good glycemic control. Insulin therapy is considered to be the best option available for attaining glycemic control. But, whether insulin therapy has achieved it is an important question to be addressed.Objective: To assess the glycemic control in subjects with diabetes on insulin therapy.Materials and Methods: A cross-sectional study was done at Karnataka Institute of Endocrinology and research, Bangalore, in 448 diabetic patients who were on insulin therapy as a part of their diabetic therapy. Data collected was analyzed using SPSS 22 version software.Results: Majority of the subjects were men (61.38%) and in the age group of > 60 years (44.9%). Many of the subjects on insulin therapy had duration of diabetes > 5 years, with 36.4% having duration of 10-20 years, while another 36% had duration of 5 -10 years. Premixed insulin (81.47%) was the most commonly used insulin regimen. 82.6% of the subjects were on conventional insulin and only 13.2% were on insulin analogues. Insulin syringe was the most commonly used delivery device, with 64.7% of subjects using it, while insulin pen was used by 33.5% subjects. Despite of insulin therapy, the glycemic control was poor and 81.4% had HbA1c >8%. Only 5.7% of the subjects had HbA1c <7%. 94.9% of the subjects reported that they were regular with their insulin therapy. Only 20.1% adjusted the insulin dose by self.Conclusions: The present study has found that despite being on insulin therapy, large percentage of subjects was unable to achieve good glycemic control.